Life-saving furniture during an earthquake. Intelligent, interconnected and interacting - Lucia Pietroni; Jacopo Mascitti; Daniele Galloppo (Agathón)
In earthquake-affected areas, the process of securing historic buildings is complex, requires large investments and long lead times. A systemic and interdisciplinary approach to the design of ‘anti-seismic’ furniture for public contexts, such as schools and offices, in areas of high risk, could be an alternative solution for the protection of people, developing a system of smart and interconnected furniture capable of acting as a life-saving passive protection device. The furniture thus conceived becomes a product-service useful for safeguarding, locating and finding people under the rubble and monitoring the building. The Industrial Research project ‘S.A.F.E. – Sustainable design of anti-seismic furniture as smart life-saving systems during an earthquake’ is part of this scenario.